2020
DOI: 10.3390/a13080181
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimal Calculation of the Rice Coding Parameter

Abstract: In this article, we design and evaluate several algorithms for the computation of the optimal Rice coding parameter. We conjecture that the optimal Rice coding parameter can be bounded and verify this conjecture through numerical experiments using real data. We also describe algorithms that partition the input sequence of data into sub-sequences, such that if each sub-sequence is coded with a different Rice parameter, the overall code length is minimised. An algorithm for finding the optimal partitioning solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thanks to this driver and the CoAP [41] and 6LoWPAN [42] libraries of RIOT-OS, the three Micromole IoT devices and its gateway establish an autonomous 6LoWPAN Wireless Sensor and Actuator Network (WSAN). In order to reduce energy consumption, sensor measurements are compressed using the algorithm described in [43].…”
Section: Sensors Telecommunications and Data Processing Modulementioning
confidence: 99%
“…Thanks to this driver and the CoAP [41] and 6LoWPAN [42] libraries of RIOT-OS, the three Micromole IoT devices and its gateway establish an autonomous 6LoWPAN Wireless Sensor and Actuator Network (WSAN). In order to reduce energy consumption, sensor measurements are compressed using the algorithm described in [43].…”
Section: Sensors Telecommunications and Data Processing Modulementioning
confidence: 99%
“…By investigating the best log-likelihood distribution of the residual, we found that the two most likely estimators are a negative binomial and geometric distribution. The likelihoods of both distributions are similar; thus, we consider the rice coding [24] a suitable entropy encoder for the residuals. See Eq.…”
Section: A Lossless Compression For Pressure Datamentioning
confidence: 99%
“…Encoding a number x works by computing so that , with q being the integer part and p the remainder, and then by coding q with a unary coding (i.e., q bits set to 1 followed by a single bit set to 0) and the remainder p of the division using r bits in standard binary. Of course, storing large q is way less efficient than storing large p , so the efficiency of the compression strongly depends on the parameter r which sets the trade-off between the magnitudes of q and p , and that can be optimally computed based on the statistics of the data [ 26 ]. To partially overcome the inefficiency of storing large q , the exponential-Golomb methods uses a variable length binary encoding method, whereas is simply written down in binary using the minimum possible number of bits, i.e., , and the actual number of bits used (minus 1) is indicated by preceding it with the same number of 0 bits.…”
Section: Related Workmentioning
confidence: 99%